2010
DOI: 10.1002/jsfa.4144
|View full text |Cite
|
Sign up to set email alerts
|

Red mold dioscorea-induced G2/M arrest and apoptosis in human oral cancer cells

Abstract: RMDE treatment inhibited the growth of SCC-25 cells by arresting cell cycle at the G2/M phase and induced apoptosis in a time- and dose-dependent manner. Therefore RMDE may be a good candidate for development as a dietary supplement against oral cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…MTT solution as added to each well for an additional incubation of 4 h at 37°C. After the addition of DMSO, the absorbance at 570 nm (formation of formazan) was measured (Hsu et al 2010). Furthermore, cells were treated by Abeta25-35 (1, 10, 25, and 50 μM) with or without samples for different times, and the protection effects of samples against Abeta-induced Neuro-2A cell damage were investigated in following experiments.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…MTT solution as added to each well for an additional incubation of 4 h at 37°C. After the addition of DMSO, the absorbance at 570 nm (formation of formazan) was measured (Hsu et al 2010). Furthermore, cells were treated by Abeta25-35 (1, 10, 25, and 50 μM) with or without samples for different times, and the protection effects of samples against Abeta-induced Neuro-2A cell damage were investigated in following experiments.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…Both pathways are executed by caspases that are activated specifically in apoptotic cells (Ashkenazi and Dixit, 1998;Green and Reed, 1998;Okada and Mak, 2004;Philchenkov, 2004;Sharifia et al, 2009;Hsu et al, 2010Milojkovic et al, 2013. J Renuka Devi reported that SFN down-regulated the expression of bcl-2 (antiapoptotic), while up-regulating p53 and Bax (proapoptotic) proteins, as well as caspase-3 (Devi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…MTT solution as added to each well for an additional incubation of 4 h at 37 C. After the addition of DMSO, the absorbance at 570 (formation of formazan) was measured (Hsu et al, 2010).…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…Cells were analysed by flow cytometry. Untreated cells were used as the control for double staining (Hsu et al, 2010).…”
Section: Apoptosis Analysismentioning
confidence: 99%
See 1 more Smart Citation